Czytelnictwo młodzieży jako problem i wyzwanie dla bibliotek publicznych = Youth reading as a problem and challenge for public libraries - Wawryk, Joanna (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
A librarian working with youth should not only ?hand out books? but act as a guide who understands teenagers? needs and creates an engaging reading environment. Essential skills include interpersonal competence, knowledge of young people?s interests, collaboration, and creative use of different media, including the internet. A librarian does not need to read every book but should be familiar with the collection and able to match books to readers. Building a young person?s ?inner library? ? a continuous path of reading from childhood through adolescence to adulthood ? is crucial. Books should engage emotions, foster passions, and help shape values. Youth libraries must consider current interests, survey results, popularity rankings, and expert recommendations when curating collections. Events, workshops, and promotional activities increase library appeal and encourage reading. Literature should address developmental and initiatory needs while cultivating lifelong reading habits. The librarian serves as a guide, advisor, and promoter of books, connecting traditional reading with new media. Ultimately, the young reader develops an ?inner library? ? a personal collection of texts that shapes knowledge, imagination, and worldview.
Keywords: bibliotekarze; czytelnictwo; książki; młodzież; internet; media cyfrowe; edukacja literacka; promocja czytelnictwa; kultura czytelnicza; librarians; reading; books; youth; digital media; literary education; promotion of reading; reading culture